2011
DOI: 10.1111/j.1600-0447.2011.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

The 7‐year course of depression and anxiety in the general population

Abstract: Course trajectories were more favorable than expected, although comorbidity resulted in poorer course. Neuroticism, physical functioning, and childhood adversity predicted an unfavorable course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
64
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 35 publications
10
64
1
1
Order By: Relevance
“…First, we investigate the average courses over time, to gain insight into the average change or stability in positive mental health and psychopathological symptoms during the course of nine months. We hypothesize that, on average, both positive mental health and psychopathology show stability over time, in line with studies on emotional well-being (Diener et al, 2006;Eid & Diener, 2004;Fujita & Diener, 2005) and psychopathology (e.g., Merikangas et al, 2003;Rhebergen et al, 2011), and in accordance with the relatively short time-span and the general and representative sample of adults. We expect the levels and courses of positive mental health and psychopathology to be negatively correlated, in line with earlier studies (e.g., .…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…First, we investigate the average courses over time, to gain insight into the average change or stability in positive mental health and psychopathological symptoms during the course of nine months. We hypothesize that, on average, both positive mental health and psychopathology show stability over time, in line with studies on emotional well-being (Diener et al, 2006;Eid & Diener, 2004;Fujita & Diener, 2005) and psychopathology (e.g., Merikangas et al, 2003;Rhebergen et al, 2011), and in accordance with the relatively short time-span and the general and representative sample of adults. We expect the levels and courses of positive mental health and psychopathology to be negatively correlated, in line with earlier studies (e.g., .…”
Section: Introductionsupporting
confidence: 84%
“…Studies on psychopathology show similar findings. Psychopathology such as depression and anxiety is relatively stable, mainly when comorbidity is present (e.g., Merikangas et al, 2003;Rhebergen et al, 2011). Although these findings indicate that emotional well-being and psychopathology are relatively stable, yet amenable for change, there are no studies that investigate the longitudinal course of positive mental health by including emotional, psychological, as well as social well-being, nor studies that directly compare the longitudinal courses of positive mental health and psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety and depression are highly comorbid at both subthreshold and threshold levels (Das-Munshi et al, 2008;De Graaf et al, 2002;Kessler et al, 2005Kessler et al, , 1994Piccinelli et al, 1999;Preisig et al, 2001;Spijker et al, 2010), anxiety disorders and depressive disorders share a genetic vulnerability (Hettema et al, 2006), and diagnostic conversions occur over time from anxiety disorders to depressive disorders and vice versa (Hagnell and Grasbeck, 1990;Merikangas et al, 2003;Rhebergen et al, 2011). These findings have raised the fundamental question of whether it is justified to regard anxiety and depressive disorders as different disease concepts.…”
Section: Inconsistency In Nomenclature Between Subthreshold and Thresmentioning
confidence: 99%
“…Finally, we explored the characteristics of each identified class and examined putative predictors of class membership, and hence course trajectory. In previous studies, sociodemographics, co-morbid anxiety disorders (Hayden & Klein, 2001), age of onset of depressive symptoms (Klein et al 1999 ;Angst et al 2009), childhood adversity (Hayden & Klein, 2001 ;Rhebergen et al 2011), somatic co-morbidity (Angst et al 2009), neuroticism (Hayden & Klein, 2001 ;Rhebergen et al 2011) and a family history of depression (Klein et al 1999 ;Stoolmiller et al 2005 ;Olino et al 2010) have been demonstrated to predict course trajectories. However, some inconsistencies exist.…”
Section: Introductionmentioning
confidence: 99%